The influence of lymphoid reconstitution kinetics on clinical outcomes in allogeneic stem cell transplantation. Issue 12 (2nd December 2018) - Kobulnicky, David J.; Sabo, Roy T.; Sharma, Shashank; Shubar Ali, Ali S.; Kobulnicky, Kristen M.; Roberts, Catherine H.; Clark, William B.; Chung, Harold M.; McCarty, John M.; Toor, Amir A.
Abstract: Lymphoid recovery following myeloablative stem cell transplantation (SCT) displays a logistic pattern of exponential growth followed by a plateau. Within this logistic framework, lymphoid recovery is characterized by the parameters R (slope of ascent), a (time of maximal rate of ascent) and K ( plateau), the 'steady-state' lymphocyte count. A retrospective analysis of allogeneic SCT performed from 2008 to 2013 was undertaken to compare lymphoid recovery and clinical outcomes in 131 patients with acute myelogenous leukemia, acute lymphocytic leukemia, and myelodysplastic syndromes. Using Prism software, a logistic curve was successfully fit to the absolute lymphocyte count recovery in all patients. Patients were classified according to the magnitude and rate of lymphoid recovery; pattern A achieved an absolute lymphocyte counts (ALC) of >1000/μL by day 45, pattern B an ALC 500 < x < 1000/μL, and pattern C an ALC <500/μL. Pattern A was characterized by a higher mean K (p < .0001) compared with patterns B and C. Patients with patterns B and C were more likely to have mixed T cell chimerism at 90 d following SCT ( p = .01). There was a trend towards improved survival (and relapse-free survival) in those with pattern A and B at 1 year compared to pattern C ( p = .073). There was no difference in cGVHD ( p = .42) or relapse ( p = .45) between pattern types. Cytomegalovirus (CMV), aGVHD, and all relapse were heralded by deviation from logistic behavior. Pattern C patients were more likely to require donor lymphocyte infusion (DLI) ( p = .017). Weaning of tacrolimus post-transplant was associated with a second, separate logistic expansion in some patients. This study demonstrated that lymphoid reconstitution follows a prototypical logistic recovery and that pattern observed correlates with T cell chimerism and need for DLI, and may influence survival.